Direct comparison of the aging and memory effects of magnetic nanoclusters and nanoparticles - Sankar, C. Raj; Vijayanand, S.; Verma, Seema; Joy, Pattayil Alias (Solid State Communications, 2007)
The magnetic characteristics of a dense magnetic nanoparticle system and a spin glass system consisting of magnetic nanoclusters are compared. Zero field cooled and field cooled magnetization measurements, including aging and memory experiments, of the nanoparticle and the magnetic cluster systems show similar characteristics, suggesting a common origin for the spin glass-type behavior of the magnetic nanoparticle and nanocluster systems. (C) 2006 Published by Elsevier Ltd.
Keywords: Magnetic nanoparticles; magnetic properties; spin glasses

Magnetic and Mossbauer spectroscopic studies of NiZn ferrite nanoparticles synthesized by a combustion method - Sreeja, V.; Vijayanand, S.; Deka, Sasanka; Joy, Pattayil Alias (Hyperfine Interactions, 2008)
The properties of nanocrystalline Ni(0.5)Zn(0.5)Fe(2)O(4) synthesized by an auto-combustion method have been investigated by magnetic measurements and Mossbauer spectroscopy. The as-synthesized single phase nanosized ferrite powder is annealed at different temperatures in the range 673-1,273 K to obtain nanoparticles of different sizes. The powders are characterized by powder X-ray diffraction, vibrating sample magnetometer, transmission electron microscopy and Mossbauer spectroscopy. The as-synthesized powder with average particle size of similar to 9 nm is superparamagnetic. Magnetic transition temperature increases up to 665 K for the nanosized powder as compared to the transition temperature of 548 K for the bulk ferrite. This has been confirmed as due to the abnormal cation distribution, as evidenced from room temperature Mossbauer spectroscopic studies.
Keywords: Ferrite; magnetic properties; Mossbauer spectroscopy; Nanoparticles